A convergence computational scheme for optimal control problems governed by Schrödinger equations. (1st January 2013) - Borzabadi, Akbar Hashemi; Heidari, Mohammad
In this paper, a numerical scheme for obtaining approximate solutions of optimal control problems governed by Schrödinger equations is presented. In this method, by considering a partition of the control space, discrete form of the problem is converted to a quasi assignment problem. Then using an evolutionary algorithm, approximate optimal control is obtained as a piecewise linear function. The comparison between the numerical solution and the exact solution for the test cases shows the good accuracy of the presented method.